What are the key determinants of nonperforming loans in CESEE? - Petr Jakubík; Thomas Reininger (Charles University in Prague, Institute of Economic Studies (IES), 2014)
Credit risk assessment is a crucial part of macroprudential analysis, with the aggregate nonperforming loan (NPL) ratio serving as a proxy for the economy-wide probability of default of the banking sector's overall loan exposure. Therefore, the factors driving the NPL ratio deserve a lot of interest. This study provides a macroeconomic model for nonperforming loans (NPLs) for the Central, Eastern and Southeastern European (CESEE) countries. It is based on panel data for Bulgaria, Croatia, the Czech Republic, Hungary, Poland, Romania, Russia, Slovakia and Ukraine. In line with current literature, our empirical analysis confirms that economic growth is the main driver that is negatively correlated with NPL development. This inverse relation is also indicated by the stock index as a leading indicator for economic developments. However, there are also other important determinants that can help explain the change in NPL ratios in the CESEE countries: past credit growth as well as exchange rate changes coupled with the share of foreign currency loans in total loans. This study confirms and quantifies risk of excessive credit growth as well as foreign exchange lending.
Keywords: G28; G32; G33; G38; 330; nonperforming loans; credit risk; financial stability; macroprudential framework; Central; Eastern and Southeastern Europe (CESEE); emerging Europe